\frac{2x-3}{x}" alt="-x> \frac{2x-3}{x}" align="absmiddle" class="latex-formula">
![\frac{2x-3}{x}+x<0|*x\neq0 \frac{2x-3}{x}+x<0|*x\neq0](https://tex.z-dn.net/?f=%5Cfrac%7B2x-3%7D%7Bx%7D%2Bx%3C0%7C%2Ax%5Cneq0)
![\frac{x^{2}+2x-3}{x}<0 \frac{x^{2}+2x-3}{x}<0](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E%7B2%7D%2B2x-3%7D%7Bx%7D%3C0)
![\frac{(x-1)(x+3)}{x}<0 \frac{(x-1)(x+3)}{x}<0](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-1%29%28x%2B3%29%7D%7Bx%7D%3C0)
_ + - +
______________-3_____________0_______________1____________________
![(-\infty;-3)\cup(0;1) (-\infty;-3)\cup(0;1)](https://tex.z-dn.net/?f=%28-%5Cinfty%3B-3%29%5Ccup%280%3B1%29)
(2x-5)(x+7)(x+1)>0
2(x-2,5)(x+7)(x+1)>0
- + - +
_______ -7______________ -1_____________ 2,5____________________
![(-7;-1)\cup(2,5;+\infty) (-7;-1)\cup(2,5;+\infty)](https://tex.z-dn.net/?f=%28-7%3B-1%29%5Ccup%282%2C5%3B%2B%5Cinfty%29)
![(\sqrt{6}-2,5)(7-6x)(2\sqrt{7}-5)<0 (\sqrt{6}-2,5)(7-6x)(2\sqrt{7}-5)<0](https://tex.z-dn.net/?f=%28%5Csqrt%7B6%7D-2%2C5%29%287-6x%29%282%5Csqrt%7B7%7D-5%29%3C0)
,т.к. ![2,5^{2}=6,25 2,5^{2}=6,25](https://tex.z-dn.net/?f=2%2C5%5E%7B2%7D%3D6%2C25)
, т.к. ![5^{2}=25 5^{2}=25](https://tex.z-dn.net/?f=5%5E%7B2%7D%3D25)
7-6x=6(7/6 -x)<0</p>
+ -
------------ 7/6---------------
-*+*-=+ -*-*-=-
![(7/6;+\infty) (7/6;+\infty)](https://tex.z-dn.net/?f=%287%2F6%3B%2B%5Cinfty%29)